Ta'zir Uang pada Santri di Pondok Pesantren Perspektif Hukum Islam: Studi kasus di Pondok Pesantren Al-Bukhori Ganjaran Gondanglegi Malang - Ahmad Muhtar Syarofi; Wildan Ulin Niam (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This research aims to describe and analyze the implementation of ta'zir punishment in the form of monetary fines for students (santri) at Pondok Pesantren Raudlatul Ulum Al-Bukhori Ganjaran Gondanglegi Malang. The focus is on how the sanction mechanism is implemented and whether it aligns with the principles of fiqh muamalah, particularly justice, public interest (maslahah), and transparency within Islamic law.The research employs a qualitative approach with a case study method. Data collection techniques include direct observation, in-depth interviews with boardingschool administrators and students, and documentation from the institution. This approach was chosen to comprehensively portray the practice of monetary fines as a disciplinary tool and to better understand the context of its implementation. The findings reveal that monetary ta'zir has become an integral part of the disciplinary system in the pesantren. Fines are imposed systematically, transparently, and fairly, based on internal deliberations and written regulations.The amount of the fine is proportional to the violation committed, and the collected funds are used for communal purposes such as maintaining the facilities of the boarding school. This practice does not contradict the principles of fiqh muamalah as long as it upholds justice and avoids oppression. It also plays a role in fostering discipline, responsibility, and social awareness among students, thus serving as an effective moral development tool aligned with the values of sharia